Determinants of smallholders’ adoption of off-season vegetable production technology in Okhaldhunga District of Nepal - Kunwar, B.; Dhakal, D.; Panta, H. K. (Journal of the Institute of Agriculture and Animal Science, 2018)
Mid-hills of Nepal is potential for off-season vegetable production but still the number of off-season vegetable growers is few and production is nominal which cannot even fulfill the internal demand. This paper examines the factors that influence farm households’ decisions for adoption of off-season vegetable production. Household questionnaires were administered to 100 farmers of Okhaldhunga district of Eastern mid-hill of Nepal. Probit regression model is used to determine the factors. The result showed that years of schooling, years of vegetable production, access to extension services, training received are the factors that significantly influence technology adoption decisions of farm households’ in the study area. It is concluded that farm households’ off-season vegetable production depend on socioeconomic characteristics of farm household and institutional effectiveness. We recommend that policies should be formulated to take advantage of factors that positively influence farmers’ adoption decisions and to mitigate the negative ones. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 221-228